The effect of omega-3 fatty acids on alcohol-induced damage - Serrano, Maitane; Rico-Barrio, Irantzu; Grandes, Pedro (Frontiers in Nutrition, 2023)
Alcohol is the most widely consumed psychoactive substance in the world that has a severe impact on many organs and bodily systems, particularly the liver and nervous system. Alcohol use during pregnancy roots long-lasting changes in the newborns and during adolescence has long-term detrimental effects especially on the brain. The brain contains docosahexaenoic acid (DHA), a major omega-3 (n-3) fatty acid (FA) that makes up cell membranes and influences membrane-associated protein function, cell signaling, gene expression and lipid production. N-3 is beneficial in several brain conditions like neurodegenerative diseases, ameliorating cognitive impairment, oxidative stress, neuronal death and inflammation. Because alcohol decreases the levels of n-3, it is timely to know whether n-3 supplementation positively modifies alcohol-induced injuries. The aim of this review is to summarize the state-of-the art of the n-3 effects on certain conditions caused by alcohol intake, focusing primarily on brain damage and alcoholic liver disease.